Socio-demographic factors, health risks and harms associated with early initiation of injection among people who inject drugs in Tallinn, Estonia: evidence from cross-sectional surveys. - Vorobjov, Sigrid; Des Jarlais, Don C; Abel-Ollo, Katri; Talu, Ave; Rüütel, Kristi; Uusküla, Anneli (The International journal on drug policy, 2013)
To explore socio-demographic factors, health risks and harms associated with early initiation of injecting (before age 16) among injecting drug users (IDUs) in Tallinn, Estonia.
Keywords: Adolescent; Adolescent Behavior; Adult; Age Factors; Child; Cross-Sectional Studies; Demography; Estonia; Female; HIV Seroprevalence; Humans; Male; Risk Factors; Risk Reduction Behavior; Risk-Taking; Substance Abuse, Intravenous